Perjuangan dan Kegigihan Nyai Ageng Serang dalam Perang Diponegoro Tahun 1825-1830 - Wulan Dari; Ira Pramudawardhani; Andriyanto Andriyanto (Universitas Veteran Bangun Nusantara, 2022)
This study aims to determine the form of struggle carried out by Nyai Ageng Serang, to find out the role of Nyai Ageng Serang in the Diponegoro war in 1825-1830 to find out how Nyai Ageng Serang was initially involved in the rebellion led by Prince Diponegoro. Research and writing about the persistence and struggle of Nyai Ageng Serang in the Diponegoro war in 1825-1830 using the Historical Research Method. From this research, it can be concluded that Nyai Ageng Serang is a female warrior figure whose education in her family environment is anti-colonial. Made Nyai Ageng Serang one of the rebels in the Diponegoro war to expel the Dutch from Indonesia. And there are values that can be taken in the struggle of Nyai Ageng Serang, including Nationalism, Patriotism, and persistence and struggle.